THE STUDY OF THE KUSHAN KINGDOM BY RESEARCHERS - Sobirov Jamshidbek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article will talk about the study of the ancient Kushan Kingdom by researchers and the fact that as a result of this, unique monuments of the Kushan Kingdom were found.